Age-related and Gender Aspects of Inflammatory Bowel Diseases in the Republic of Dagestan - S. Sh. Akhmedkhanov; G. H. Abakarova; A. T. Beibalayeva; B. S. Abdullayeva; Z. M. Saidova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: Creation of a patient registry in the Republic of Dagestan to study various aspects of the course and outcomes of IBD, depending on the age and gender of patients.Materials and methods. We have created a register of IBD patients in the Republic of Dagestan. It included 168 IBD patients aged 17 to 70 years, 69 males and 99 females, the average age of patients with IBD was 38.1 ± 2.5 years with an average duration of illness of 6.19 ± 0.71 years. The diagnosis of IBD was established on the basis of the characteristic clinical picture of the disease, objective status, results of laboratory, endoscopic, X-ray and morphological research in accordance with Russian Clinical GuidelinesResults. The prevalence of IBD in the Republic of Dagestan is 5.41 cases per 100,000 population. The progression of IBD is more often observed in women, aged 30 to 39 years, residents of rural areas. Anemia (mainly chronic iron deficiency) was registered in 66.1 %, more often in women, its maximum frequency was noted in patients aged 20–29 years (80 %). Disability due to IBD was registered in 55.4 % of patients.Conclusions. The creation of a register of IBD patients in the Republic of Dagestan is aimed at monitoring the state of health, timely monitoring of the effectiveness of therapy and improving the quality of medical care.